Model of Formation of Professional Communication Culture of Future Social Workers in Conditions of Higher Education - N V Kurilovich (Peoples' Friendship University of Russia (RUDN University), 2011)
The article considers the structurally functional model of the formation of professional communication culture of the future social workers in the higher education developed by the author. The offered model is based on theoretical-methodological approaches, and represents the integral, open, pedagogical system serving as a constituent component of the entire process of vocational training of the social worker and being distinguished by the unity of target, conceptual, contents, criterion-assessment and productive blocks.